Penguatan Literasi Dan Bekal Dasar Moderasi Beragama Sejak Dini Di Sekolah Dasar Negeri Banjiran - Zuyyina Amalia Mustaqim; In’am Mujahidin; Muhammad Agil Al Hadif; Ahmad Yusuf Sholah; Tamma Yaktafia; Insaniyah Masykuri; Faiha Irana; Bagas Heradhyaksa (Lembaga Pengembangan Kinerja Dosen, 2024)
Walisongo State Islamic University KKN students held a socialization on the importance of literacy and basic provisions for religious moderation from an early age at the banjiran public elementary school where the purpose of this socialization was carried out to provide a deep understanding to teachers, students about the importance of religious literacy in shaping the character of good and religious children. Religious moderation literacy is the ability to understand, interpret and apply religious teachings in a balanced and tolerant manner. Religious moderation literacy also includes the ability to communicate effectively about the values of moderation and to coexist harmoniously with individuals from various religious backgrounds. In this socialization, learning media such as videos, summary materials in the form of power points and also educational applications are used to convey the values of religious moderation.